A comparison of outcomes between laparoscopic and open adrenalectomies in dogs. (8th January 2021) - Taylor, Colin J.; Monnet, Eric
Abstract: Objective: To compare short‐ and long‐term outcomes of dogs with adrenal tumors treated by adrenalectomy with laparoscopy or laparotomy. Study design: Retrospective study of dogs that underwent adrenalectomy with laparoscopy or laparotomy. Sample population: Fourteen dogs treated with laparoscopic adrenalectomy (LA) and twenty‐six dogs treated with open midline adrenalectomy (OA). Methods: D ogs treated with LA were matched with 1 or 2 dogs treated with OA on the basis of histological nature, size, and side of the tumor. Intraoperative complications, postoperative complications, and long‐term survival were compared between LA and OA. Results: Intraoperative hypotension occurred in 2 of 14 (14.3%) dogs in the LA group and in 16 of 26 (61.5%) dogs in the OA group ( P = .007). The surgical time was 69.8 ± 21.8 minutes for the LA group and 108.6 ± 42 minutes for the OA group ( P = .0003). The hospitalization time was 39.3 ± 14.9 hours for the LA group and 46.3 ± 25.1 hours for the OA group ( P = .1453). The 1‐ and 2‐year survival rates were 77% and 77%, respectively, for the LA group and 77% and 66%, respectively, for the OA group ( P = .6144). Conclusion: Laparoscopic adrenalectomy was associated with a shorter surgical time and a reduced incidence of hypotension compared with open adrenalectomy in this case‐matched study. Short‐ and long‐term outcomes were not affected by the surgical technique used to complete the adrenalectomy. Clinical significance: Laparoscopy can be recommended for adrenalectomy in dogs; however, appropriate case selection is required.